Excavating Organizational Assumptions about Cultural Change: The Unintended Consequences of Safety Committee Initiatives - Gosen, Dora; Mielly, Michelle (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2021)
This study contributes to the emerging literature on the interplay between safety committees and employee perceptions of organizational safety culture. Creating, managing and maintaining a safety culture in organizations involves significant investment in the establishment of safety committees. The role of such committees in improving safety culture perceptions has remained underexplored in the safety management and organizational literature.This study addresses that gap and focuses on a safety committee within the facilities management operations of a large American academic institution. The objective is to generate understandings of how a committee can influence organizational cultural change and impact employee perceptions of safety.Using Schein’s organizational culture model as a prism, we unpack the employees’ implicit cultural beliefs. Data from over sixty employee interviews revealed that formation of the Safety Committee resulted in unintended consequences in terms of employee perceptions.Employees attributed most safety-related actions to the committee when, in fact, the managers and supervisors had actually carried them out. This overestimation of committee activities and concomitant underestimation of managerial actions by employees was an unintended consequence of establishing a committee. Employees, in fact, collectively attributed all positive changes in the organizational culture to the committee. The committee ultimately influenced the employees’ basic assumptions, such change being, according to Schein, a prerequisite for organizational cultural change.This study, therefore, contributes to the literature by proposing that unintended consequences can operate in three different ways to support organizational change. First, unintended consequences can promote positive outcomes; second, they can reveal a new understanding of committees, which under certain circumstances can act as a proxy for management and encourage positive perceptions of managerial commitment. Lastly, unintended consequences can provide a means to detect and ‘excavate’ hidden, implicit assumptions that drive organizational culture’s deepest layers.